Amazons and Victims: Resisting Wife-Abuse in Working-Class Montréal, 1869-1879 - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractWhen Canadian feminists first began to organise against domestic violence in the 1970s, there was a sense that they were the first to do so. What this article suggests is that resistance to wife-abuse had its roots in the nineteenth century. Its visibility was, in part, due to the efforts of the temperance movement which made wife-battering into a public issue by linking it to its antidrinking campaign. Drunkedness was thought to cause wife-abuse and, as such, shaped people's perceptions of it as a crime. The first half of this article describes the role of temperance ideas informing the public's attitudes towards wife-battering. A common perception was that women beaten by their husbands were passive victims. This was only a part of the story. The actions of a significant number of working-class women in Montréal reveal a competing narrative. Evidence found in Montréal newspapers, police reports, and judicial records showed that women did, indeed, resist their husbands' violence. What sustained these women in their struggles against the physical aggression of their husbands, and the forms which these struggles took, are the subject of the second half of the paper.